RETRACTED: A time varying constrict factor PSO algorithm research - Huang, Gewen; Cai, Yanguang; Cai, Hao (Journal of computational methods in sciences and engineering, 2018)
This article has been retracted, and the online PDF has been watermarked ``RETRACTION''. The retraction notice is available at http://doi.org/10.3233/JCM239001.